The convicts' contribution to the built environment of colonial Western Australia between 1850-1880 - Bush, Fiona (Curtin University, 2012)
Western Australia was founded as Australia’s first free colony in June 1829. The colony was not as successful as those in eastern Australia, and many of the settlers argued that the poor progress was due in part to a shortage of labourers. By 1849 the colonists had decided that their only way forward was to become a penal colony and the first ship arrived in June 1850 carrying 75 convicts.The thesis explores the impact that convicts had on the built environment of Western Australia. To understand the convicts’ contribution to the building industry this thesis begins with a study of buildings constructed before 1850. Extensive research was undertaken into the types of buildings erected by the settlers between 1829 and 1850: such as the types of materials used, the design and who actually constructed the buildings. The study found that before the arrival of the convicts the colony had a shortage of men with skills in the building trade. One of the major factors that enabled the convicts to contribute to the development of the colony’s building industry was vocational training, in areas such as bricklaying, brickmaking, carpentry and masonry that they obtained during their incarceration in public works prisons in Britain.This training was provided by the British government before the convicts were transported to a penal colony, as part of a new system of penal discipline. Following their arrival in Western Australia, soldiers of the Royal Engineers continued the convicts’ training on public works projects in the colony.This thesis expands our knowledge of how the convict system operated in Western Australia, especially how it differed from that used in Australia’s eastern colonies. It highlights the integral part that the Royal Engineers had in the convicts’ training, a role not previously investigated. The examination of how ticket--‐of--‐leave men (convicts out on parole) were utilised by private settlers indicated that there were considerable flow--‐on effects for the private citizen, not just for public projects. In particular, the research has shown that the skills gained by the convicts while erecting government colonial buildings were of direct benefit to the settlers. One important and far--‐reaching benefit was the substitution of brick for rammed earth or wattle and daub.Finally, the thesis used an archaeological methodology to analyse and compare two groups of buildings; those constructed before 1850 and those constructed after 1850. This use of archaeological methods to analyse standing structures is considerably under--‐utilized in Western Australia.